Adaptive Concrete Beams Equipped With Integrated Fluidic Actuators - Kelleter, Christian; Burghardt, Timon; Binz, Hansgeorg; Blandini, Lucio; Sobek, Werner (Frontiers in Built Environment, 2020)
The rapidly growing world population is a great challenge for the building industry. With the scarcity of resources, it is not possible to provide the upcoming humanity with sufficient living- and work places and infrastructure with current construction methods. For wide-spanning beams and slabs the decisive design criteria is mainly determined by deformations rather than stresses, since deflections must be limited. This leads to structural elements, which are not fully exploited. However, if the deformations can be reduced significant material savings can be achieved. This article presents a solution, which allows beams to react actively to loads by use of integrated actuators. Sensors, actuators and a control unit enable components subjected to bending to adapt to these loads. The newly developed integrated hydraulic actuators allow the structure to react specifically to any possible load, by adjusting the internal hydraulic pressure. This is an enormous advantage in load bearing systems because there is often no dominant load case. This internal actuation concept is a new approach, as previous adaptive structures either have externally added actuators or compose of truss structures in which single bars are actuated. In this paper the concept is explained analytically, simulated with the finite element method and validated experimentally.